Reduction of Cu-rich interfacial layer and improvement of bulk CuO property through two-step sputtering for p-CuO/n-Si heterojunction solar cell - Masudy-Panah, Saeid (2014)
Copper-rich interfacial-layer (Cu-rich IL) is formed during sputter deposition of cupric oxide (CuO) layer on silicon (Si). It has significant impact on the performance of p-CuO/n-Si heterojunction solar cells. In this report, CuO films deposited on Si at different RF-power levels using single and two-step RF-sputtering techniques and p-CuO/n-Si heterojunction solar cells have been investigated. Systematic characterization using XPS, AFM, XRD, Raman, and HR-TEM reveal that two-step RF-sputtering technique offers better crystal quality CuO film with thinner Cu-rich IL layer. Photovoltaic (PV) properties with an open-circuit voltage (Voc ) of 421 mV, short circuit current (Jsc ) of 4.5 mA/cm2, and a photocurrent of 8.3 mA/cm2 have been achieved for the cells prepared using two-step sputtering method, which are significantly higher than that for the solar cells fabricated using a single-step sputtering. The PV properties were further improved by depositing CuO films at higher working pressure with nitrogen doping. The efficiency of the best device achieved is approximately 1.21%, which is the highest value reported for p-CuO/n-Si heterojunction based solar cells.